PERANAN VALUASI EKONOMI DALAM MENEKAN KERUSAKAN SUMBER DAYA ALAM DAN PEMBANGUNAN BERKELANJUTAN - Nazwa Aulia; Adelia Marta Lubis; Legi Likasri Simbolon; Bonaraja Purba (STKIP Subang, 2026)
The challenge of balancing economic, social, and ecological interests in Indonesia's natural resource management remains an ongoing concern yet to be fully resolved. One approach widely regarded as capable of addressing this issue is economic valuation an analytical framework that transforms the value of natural resources and ecosystem services into measurable monetary figures, encompassing both directly observable and indirectly felt dimensions of benefit within a comprehensive assessment. This article specifically examines the extent to which economic valuation can be operationalized as a strategic policy instrument both to mitigate the rate of natural resource degradation and to strengthen the foundations of sustainable development at the national level. To achieve this, the study was developed through a systematic literature review employing a qualitative-descriptive approach, drawing upon eight peer-reviewed journal publications reinforced by four secondary sources comprising reference books, international institutional reports, applicable national regulatory instruments, and official government datasets. Taken together, the findings highlight three principal contributions of economic valuation: first, its capacity to map the total economic value of a given natural resource or ecosystem; second, its ability to quantify economic losses arising from environmental deterioration; and third, its potential to serve as an evidence-based foundation for the formulation of conservation-oriented regulation.